Back Cover: A Durable, Flexible, Large‐Area, Flame‐Retardant, Early Fire Warning Sensor with Built‐In Patterned Electrodes (Small Methods 4/2021). Issue 4 (14th April 2021) - Khan, Fawad; Wang, Shanchi; Ma, Zhewen; Ahmed, Adnan; Song, Pingan; Xu, Zhiguang; Liu, Riping; Chi, Huanjie; Gu, Jiayi; Tang, Long‐Cheng; Zhao, Yan
Abstract : In article number 2001040 by Pingan Song, Yan Zhao, and co‐workers, a strategy is proposed to fabricate a new type of large‐area early fire warning sensor bypatterning fire‐sensing, flame‐retardant, GO‐based coating and conductive ink in an interdigitated way on cotton fabrics. The sensor features a rapid response (<3 s), and is flexible, washable, and mechanically durable, demonstrating its great promise for very early fire warning.